Effect of Gamma Irradiation on Thermal and Tensile Properties of Teak Wood Flour/Cotton Stalk Flour and Polypropylene Hybrid Composites - Kumar, Vikram; Gulati, Kapil; Singh, Omvir; Arora, Sanjiv (Indian Forester, 2019)
Hybrid composites of teak wood flour/cotton stalk flour and polypropylene were fabricated at a fixed plastic to fiber ratio of 80:20 and variable proportions of the two fibres by extrusion method. Maleic anhydride grafted polypropylene (MAPP) was used as the coupling agent. The tensile specimens of neat PP and hybrid composites were prepared by injection moulding method. Hybrid composites were subjected to 25 kGy dose of gamma radiation. The tensile strength was estimated using Universal Testing Machine (UTM). Thermal analysis of the samples has been carried out at a heating rate of 10°C min>sup>-1, from 50°C temperature to 500°C, in an inert atmosphere. The outcome of gamma irradiation on thermal and tensile properties was analysed. A notable improvement in tensile strength and tensile modulus has been observed, with the modest decline in thermal stability. The improvement in tensile strength of hybrid composite as compared to neat PP, can be attributed to the cross linking effects of both the compatibiliser and the gamma irradiation.